Automated technology for verification and analysis : 15th International Symposium, ATVA 2017, Pune, India, October 3-6, 2017, Proceedings /: 15th International Symposium, ATVA 2017, Pune, India, October 3-6, 2017, Proceedings. (2017) - Unknown
No abstract available